2021
DOI: 10.1016/j.annonc.2021.08.585
|View full text |Cite
|
Sign up to set email alerts
|

302P Clinical implication of tissue re-biopsy in metastatic breast cancer (MBC) patients: A single centre retrospective analysis

Abstract: miRs-449 are downregulated in parental TNBC cell line and patients, and its high expression is associated with better OS (p<0.05). Luciferase assay shows that ACSL4 is a direct target of miR-449a and b. Both, ACSL4 silencing and miRs-449 gain of function, inhibit cell proliferation, colony formation, migration, invasion and sensitizes XC1 to DOX through mTOR inactivation and ABCG2 downregulation.Conclusions: This study suggests a possible role of miRs-449 family in DOX response through direct ACSL4 repression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Receptor conversion is a well-documented event in progressive MBC, which results in HR and HER2 status discordance between the primary tumor and metastatic site ( 21 ). An increasing number of guidelines recommend a re-biopsy of metastatic breast cancer to determine the receptor status and molecular subtype ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Receptor conversion is a well-documented event in progressive MBC, which results in HR and HER2 status discordance between the primary tumor and metastatic site ( 21 ). An increasing number of guidelines recommend a re-biopsy of metastatic breast cancer to determine the receptor status and molecular subtype ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The BOLERO-2, PrE0102, and GINECO studies demonstrated that everolimus plus endocrine therapy significantly prolonged PFS in postmenopausal HR-positive and HER2-negative advanced BC patients who failed endocrine therapy [ 75 77 ]. Meanwhile, BOLERO-4 and BOLERO-5 demonstrated that everolimus, in combination with letrozole and exemestane, respectively, prolonged PFS in this group of patients [ 78 , 79 ]. And the MIRACLE study depicted that everolimus plus endocrine therapy was effective in patients with premenopausal HR-positive and HER2-negative advanced BC [ 80 ].…”
Section: Clinical Data Of Studies Targeting Pi3k Pathway In Tnbcmentioning
confidence: 99%